Quality of referrals for elective surgery at a tertiary care hospital in a developing country: an opportunity for improving timely access to and cost-effectiveness of surgical care - Gyedu, Adam (Int J Surg, 2015)
INTRODUCTION: A disproportionate number of surgeries in low- and middle-income countries (LMICs) are performed in tertiary facilities. The referral process may be an under-recognized barrier to timely and cost-effective surgical care. This study aimed to assess the quality of referrals for surgery to a tertiary hospital in Ghana and identify ways to improve access to timely care. METHODS: All elective surgical referrals to Komfo Anokye Teaching Hospital for two consecutive months were assessed. Seven essential items in a referral were recorded as present or absent. The proportion of missing information was described and evaluated between facility, referring clinician type and whether or not a structured form was used. RESULTS: Of the 643 referrals assessed, none recorded all essential items. The median number of missing items was 4 (range 1 – 7). Clinicians that did not use a form missed 5 or more essential items 50% of the time, compared with 8% when a structured form was used (p=0.001). However, even with the use of a structured form, 1 or 2 items were not recorded for 10% of referrals and up to 3 items for 45% of referrals. CONCLUSION: Structured forms reduce missing essential information on referrals for surgery. However, proposing that a structured form be used is not enough to ensure consistent communication of essential items. Referred patients may benefit from referrer feedback mechanisms or electronic referral systems. Though often not considered among interventions to improve surgical capacity in LMICs, referral process improvements may improve access to timely surgical care.